ENHANCING REPURCHASE INTENTION THROUGH SOCIAL MEDIA, PRODUCT VARIETY, AND CAFE ATMOSPHERE: EVIDENCE FROM HERO COFFEE INDONESIA CONSUMERS IN SEMARANG CITY - Niqoo Maulana; Joko Riyanto; Ribut Musprihadi; Frans Sudirjo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of social media marketing, product variety, and café atmosphere on consumer repurchase intention at Hero Coffee Indonesia. A quantitative approach was employed using a survey method with purposive sampling. The respondents consisted of Hero Coffee consumers who had made at least two purchases within the last three months and followed the café’s official social media accounts. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. The findings indicate that social media marketing, product variety, and café atmosphere each have a positive and significant effect on consumer repurchase intention. Simultaneously, the three variables also significantly influence repurchase intention, suggesting that digital engagement, diverse menu offerings, and a comfortable café environment are key drivers of customer loyalty. Theoretically, this study contributes to the development of consumer behavior models in the coffee industry, particularly in understanding factors influencing repeat purchases. Practically, the findings provide strategic insights for Hero Coffee Indonesia’s management in designing more effective marketing initiatives, optimizing product offerings, and enhancing the café atmosphere to strengthen customer retention and increase repurchase intention. Keywords: Social Media Marketing; Product Variet; Cafe Atmosphere; Repurchase Intention; Hero Coffee Indonesia